Long-term plant community responses to resource objective wildfires in montane coniferous forests of Grand Canyon National Park, USA - Springer, Judith D.; Stoddard, Michael T.; Huffman, David W.; Laughlin, Daniel C.; Fulé, Peter Z.; Daniels, Mark L. (Forest ecology and management, 2022)
•Pine-oak plant community composition after low-severity resource objective fire was most resilient but cover has declined over time.•Changes in three forest types over time since fire are likely due to long-term drought effects, tree mortality or bison impacts.•Mixed-conifer and spruce-fir plant communities appear to be in a reorganization phase differing from pre-fire conditions. Interest in use of naturally ignited wildland fires managed to meet multiple resource objectives (resource objective wildfire) is increasing among U.S. public forest managers; however, only a limited number of studies have examined this approach for conserving or restoring understory plant diversity, productivity, and community structure. We analyzed understory community changes two andtwelve yearsafter resource objective fire, using permanent sample plotsin three montane contrasting forest types in Grand Canyon National Park,AZ.Our findingsindicatedthat species compositionin the pine-oak forest rebounded to be similar to that observed before the fire, but plant cover did not recover to pre-fire levels by the twelfth year post-fire. Plant cover showed mixed results post-fire in mixed-conifer and spruce-fir forests, and species composition was still characterized by ruderal species twelve years later. Patterns observed in this study likely reflect interacting factors of burn severity, periodic drought, large ungulate herbivory, and inherent site variability. Other than cheatgrass (Bromus tectorum), we found no non-native speciesoccurring with high frequency. Continued monitoring with increased frequency and intensity could lead to better understanding of long-term changes in these forests after resource objective fire, and enhance our understanding of important drivers of variation including interactions ofclimate, burn severity and herbivory by large ungulates.